de la quema, corte, arranque, abandono o pastoreo del matorral de escoba blanca (Cytisus multiflorus) sobre la producción y estructura de la comunidad herbácea - Fernández-Santos, B; Gomez Gutiérrez, J M; Garcia Mares, R T (Pastos, 1992)
The effects of burning, cutting , pulling out, field abandonment or grazing on the pro- duction and structure of a dehesa pasture invaded by Cytisus multiflorus were studied. Significant differences in the biomass of herbaceous species were found between pastu- res and treatments when cutting was done in February. The highest total biomass pro- duction was in the "abandoned" plot. No differences were found between the burned and cut plots. All the treatments, except abandonment, gave rise to higher biomass in herbaceous plants compared to control plots, i.e. on which grazing was continued. After 3 years there was no effect of treatment on the appearance of new species. A decrease in species number was observed with the burned plot being the least affected. The área with traditional grazing showed the highest diversity, specific heterogeneity and propor- tion of leguminous species. The negative effect of cutting the above-ground biomass in winter is discussed. Key
Keywords: Biomass production; Community structure; Human disturbances treatments; Matorral pasture; Salamanca